Effectiveness of a Transtheoretical Model-Based Intervention to Improve Blood Pressure Control of Hypertensive Patients in China: A Clustered Randomized Controlled Trial - Ping Chen; Ying Shen; Chao He; Xinying Sun (Frontiers Media S.A., 2022)
BackgroundHypertension can result in great cardiovascular risk, while medication adherence and blood pressure control of patients were suboptimal. Therefore, we conducted a 12-month clustered randomized controlled trial to evaluate the effectiveness of transtheoretical model (TTM)-based health intervention mode on blood pressure of Chinese newly-diagnosed hypertensive patients.MethodsThis trial was conducted in six primary healthcare centers, Shunyi District, Beijing, China from September 2016 to September 2017. A total of 400 patients were included and randomized, 194 patients in the control group and 206 patients in the intervention group. Patients in the intervention group received TTM-based health intervention and those in the control group received usual care. Multilevel modeling was used to adjust for clustering effect and repeated measurements.ResultsSystolic blood pressure of patient was reduced by 4.534 mm Hg at 3-month follow-up [95% CI (−3.054, −1.403), p = 0.005], 3.982 mm Hg at 6-month follow-up [95% CI (−7.387, −0.577), p = 0.022], and 5.803 mm Hg at 12-month follow-up [95% (−9.716, −1.891), p = 0.004]. Diastolic blood pressure of patient was reduced by 3.383 mm Hg at 3-month follow-up [95% CI (−5.724, −1.042), p = 0.005], 0.330 mm Hg at 6-month follow-up [95% CI (−2.870, 2.210), p = 0.799], and 3.129 mm Hg at 12-month follow-up [95% CI (−6.048, −0.21), p = 0.036]. Medication adherence of patients was improved at all the three time points. For stages of change for taking medication, patients in the intervention group were 8.401-fold more likely to be in a higher stage at 3-month follow-up [95% CI (4.186, 16.862), p < 0.001]. The odds ratio of being in a higher stage was 8.454 at 6-month follow-up [95% CI (3.943, 18.123), p < 0.001] and 19.263 at 12-month follow-up [95% CI (7.979, 46.505), p < 0.001].ConclusionTranstheoretical model-based health intervention might be a promising strategy to improve medication adherence of newly-diagnosed hypertensive patients in community.